What determines the performance of small and medium-sized enterprises supply chain financing? A qualitative comparative analysis of fuzzy sets based on the technology–organization–environment framework - Duan, Weichang; Hu, Hanzhou; Zhang, Yuting (Frontiers in Psychology, 2022)
With the COVID-19 pandemic sweeping the globe, small and medium-sized enterprises’ (SMEs’) survival space has been increasingly constrained, and their financing challenges and costly concerns have also become more evident. With the emergence of the supply chain financing model, the problem of difficult financing for SMEs has been effectively alleviated. How to effectively improve the performance of supply chain financing for SMEs is a hot issue of common concern for both business and academic circles. This paper used 90 SMEs involved in supply chain financing business for a case study based on the “Technology–Organization–Environment” (TOE) framework, using fuzzy set qualitative comparative analysis (fsQCA), and explored the linkage effects of technology, organization, and environmental conditions on SMEs' performance in improving supply chain financing and their path choices. The study found that: (1) individual conditions do not constitute a necessary condition for high/low supply chain financing performance. However, technical level preconditions play a more important role in shaping the high supply chain financing performance of firms. (2) The three preconditions at the technological, organizational, and environmental levels work together to form a diverse set of conditions that drive the high supply chain financing performance of firms. That is, the paths driving the high supply chain financing performance of SMEs are characterized by "different routes to the same destination". There are three different models: "technology-supply chain capability-driven", "IT-supply chain capability-driven", and "IS-supply chain capability-driven". (3) The degree of application of corporate information technology, information sharing capability, and supply chain capability, and the lack of environmental competitiveness are the reasons for the generation of the low supply chain financing performance of SMEs. The above research findings can provide a direct theoretical basis for enterprise supply chain financing practice and are of great practical significance in guiding Chinese SMEs on how to improve their supply chain financing performance.